2007
DOI: 10.1353/eco.2007.0014
|View full text |Cite
|
Sign up to set email alerts
|

Another Pass-Through Bites the Dust? Oil Prices and Inflation

Abstract: una copia impresa con un costo de $500 si es dentro de Chile y US$12 si es para fuera de Chile. Las solicitudes se pueden hacer por fax: (56-2) 6702231 o a través de correo electrónico:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
125
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(138 citation statements)
references
References 40 publications
8
125
1
4
Order By: Relevance
“…In contrast to the generally held viewpoint that recessions and inflation are caused by an uptrend in oil prices, Barsky and Kilian [33] evidenced that the variations in oil prices do not significantly explain the stagflation in the US. Gregorio et al [26] in their study comprising of a sample of 34 countries reported a downfall in the intensity of relationship between oil prices and inflation in many of the countries under study. Chen [28] also suggested a similar decline in the oil passthrough effect in his study that included 19 industrialized economies.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast to the generally held viewpoint that recessions and inflation are caused by an uptrend in oil prices, Barsky and Kilian [33] evidenced that the variations in oil prices do not significantly explain the stagflation in the US. Gregorio et al [26] in their study comprising of a sample of 34 countries reported a downfall in the intensity of relationship between oil prices and inflation in many of the countries under study. Chen [28] also suggested a similar decline in the oil passthrough effect in his study that included 19 industrialized economies.…”
Section: Literature Reviewmentioning
confidence: 97%
“…For instance, Hamilton [1], Burbridge and Harrison [19], Loungani [20], Gisser and Goodwin [21], Mork [22], Hamilton [2], Rotemberg and Woodford [23], Hamilton [3], Cunado and Garcia [24] and [25] Bachmeier, Gregorio et al [26], Zhang and Reed [27], Chen [28] etc. are some of the studies that have tried to capture the dynamic interactions between oil price shocks, inflation and economic activity in a country but with no consensus building in their approach as well as findings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…De Gregorio et al (2007) deploy rolling VARs to examine the pass-through of global oil prices to consumer price inflation in 24 advanced and 12 emerging markets during . Their results show a fall in the average estimated pass-through for advanced economies and, to a lesser degree, for emerging economies.…”
Section: Literature Surveymentioning
confidence: 99%
“…They identify that negative oil price shocks significantly increase inflation. De Gregorio et al (2007) estimate a Phillips curve equation with lags of inflation, the output gap, and the percentage change in the price of oil for 24 industrial economies and 12 emerging economies. Their study shows the effects of oil shocks on the general level of prices.…”
Section: Previous Studiesmentioning
confidence: 99%